Demotivation factors’ differences of high school EFL learners during Covid-19 pandemic: A quantitative study - Adara, Reza Anggriyashati; Puspahaty, Novita; Nuryadi, Nuryadi; Utama, Wilda (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
Covid-19 pandemic may pose a factor that reduces learners’ motivation. The present study aims to investigate the differences between demotivation factors of public and private high school EFL learners during the Covid-19 pandemic. The present study applies a quantitative method to obtain its data by distributing a set of questionnaires adapted from Sakai and Kikuchi (2009) to 61 high school students from public and private high schools. The findings indicate that both groups of learners are mostly demotivated by inadequate school facilities, test scores, and teachers’ competence and teaching styles. It can be said that despite the differences in teaching location, learners may be demotivated by the same variables. Therefore, it seems imperative for teachers and teaching institutions to provide better school facilities, reduce learners’ anxiety during tests, and improve teachers’ competence and teaching styles to overcome students’ demotivation.  DOI: 10.26905/enjourme.v6i2.6519